An Analytical Solution for Non-Darcian Flow on a Constant Head Packer Test in the Interlayer Staggered Zone. (8th November 2021) - Shen, Qi; Zhou, Zhifang; Chen, Meng; Li, Sijia; Wang, Zhe; Li, Yabing
Abstract : Groundwater flow in an aquifer has frequently been found to be non-Darcian by performing in situ tests. A novel analytic model is proposed in this study for describing the unsteady non-Darcian flow in a confined aquifer by taking advantage of the observed flow rate and injection pressure during the constant head packer test. A linearization approximation of the Izbash equation is used to approximate the nonlinear term in the governing equation. This analytic model is applied to describe the non-Darcian flow in the interlayer staggered zone at the Baihetan hydropower station, China. The test results inversed by the genetic algorithm show that non-Darcian flow happened during the test under the injection pressure 0.3 MPa with the power index n is 1.278, non-Darcian hydraulic conductivity k 1 is 1.613 × 10 − 5 cm/s and the specific storage S s is 9.757 × 10 − 5 m -1, respectively. The sensitivity analysis indicated that when the power index n or the specific storage S s is larger, and the hydraulic head will increase more slowly and needs longer to stabilize, but the non-Darcian hydraulic conductivity k 1 shows the opposite trend. Moreover, the hydraulic head is more sensitive to the power index n compared to other parameters at late times. The findings of this study reveal the non-Darcian flow during the constant head packer test and provide a simple and fast way to estimate parameters for more accurate seepage field simulation.